Estudiar los efectos de la aplicación de n, k, mg, s, ca y mn en el cultivo del maíz híbrido ‘dekalb dk – 1040’ en la zona de Quevedo - Marcillo Marmolejo, Carlos Alberto (2011)
On the grounds of the Villa 'Salapi' property of Dr. Marcelo Marcillo Jiménez, located at km 10 of road Quevedo - Santo Domingo, Canton Buena Fe, Province of Los Rios, a trial was conducted in maize hybrid 'Dekalb DK - 1040 ', in the presence of various levels of chemical fertilizers, in order: a) evaluate the effect of nutrients N, K, Mg, S, Ca and Mn on the agronomic and yield of hybrid maize; b) identify the most appropriate treatment to maximize grain yield per unit area per unit time, c) conducting economic analysis of grain yield based on the cost of treatments. The treatments were: 160 - 60 Kg / ha of NK, 160 - 60 - 58 Kg / ha of NKMg, 160 - 60 - 58 - 29 kg / ha of NKMgS; 160-60 - 58 - 29 - 44 kg / ha NKMgSCa, 160 - 60 - 58 - 29 kg / ha of NKMgSCaMn and 92 - 23 - 30 Kg / ha of NPK.